2015
DOI: 10.1186/s12879-016-1364-y
|View full text |Cite
|
Sign up to set email alerts
|

Complex interaction between dengue virus replication and expression of miRNA-133a

Abstract: BackgroundDengue virus (DENV) is the most common vector-borne viral infection worldwide with approximately 390 million cases and 25,000 reported deaths each year. MicroRNAs (miRNAs) are small non-coding RNA molecules responsible for the regulation of gene expression by repressing mRNA translation or inducing mRNA degradation. Although miRNAs possess antiviral activity against many mammalian-infecting viruses, their involvement in DENV replication is poorly understood.MethodsHere, we explored the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 54 publications
2
49
0
1
Order By: Relevance
“…Previously, targeting of genomes of RNA viruses by host miRNAs have been reported in mammalian cells [ 41 ]. In particular, a number of human miRNAs (hsa-miR-133a, hsa-miR-548g-3p, hsa-miR-223) with potential binding sites in the 5’ and 3’UTRs of different DENV serotypes have been shown to negatively affect replication of the viruses when overexpressed in mammalian cells [ 42 , 43 ]. In mosquitoes, a midgut-specific alb-miR-281 from Ae .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, targeting of genomes of RNA viruses by host miRNAs have been reported in mammalian cells [ 41 ]. In particular, a number of human miRNAs (hsa-miR-133a, hsa-miR-548g-3p, hsa-miR-223) with potential binding sites in the 5’ and 3’UTRs of different DENV serotypes have been shown to negatively affect replication of the viruses when overexpressed in mammalian cells [ 42 , 43 ]. In mosquitoes, a midgut-specific alb-miR-281 from Ae .…”
Section: Resultsmentioning
confidence: 99%
“…We recently described a complex interaction between miR-133a and DENV replication (Castillo et al, 2016), in which we demonstrated that overexpression of miR-133a impairs DENV-2 replication in Vero cells. We also found that the 3'-untranslated regions (3'-UTRs) of DENV-1, -2, and -4 downregulated the expression of miR-133a.…”
mentioning
confidence: 79%
“…In the context of this study, our data was similar to that reported by Casseb et al (2016), indicating that transfection of the 3'-UTRs of DENV-1, -2, and -4 into Vero cells induced downregulation of the expressions of Drosha, Dicer, and TAR RNA-binding protein (TRBP), all of which are key components of the miRNA biogenesis machinery. The detailed methods for obtaining the 3'-UTRs of DENV-1, -2, and -4 fused with green fluorescent protein have been described previously (Castillo et al, 2016). Vero cells were transfected with the different 3'-UTRs and total RNA was purified.…”
mentioning
confidence: 99%
“…El primero de esos miR es muy interesante ya que está implicado en el control de la expresión de la proteína conocida como PTB (del inglés polypyrimidine tract-binding protein), la cual se ha reportado es esencial para la replicación del DENV 24 . Nuestros estudios permitieron demostrar efectivamente que la sobre-expresión del miR-133a inhibía la replicación del DENV-2 25 . Además pudimos demostrar que la infección por el DENV-2 incrementa la expresión de PTB durante las primeras horas de la infección, pero al mismo tiempo, la presencia del miR-133a contrarrestaba dicho efecto durante las primeras 12 h. Además se pudo observar que el DENV-2 inhibía la expresión endógena del miR-133a durante las primeras 8 h de la infección.…”
Section: Wwwsochinfclunclassified